An implicitly coupled hydro-geomechanical model for hydraulic fracture simulation with the discontinuous deformation analysis - Morgan, William E.; Aral, Mustafa M. (International journal of rock mechanics and mining sciences (Oxford, England : 1997), 2015)
In this article we present and verify an algorithm for modeling hydraulic fracturing in complex fracture geometries. The method is built upon an existing model which uses the discontinuous deformation analysis for simulation of rock mechanics and upon a finite volume fracture network model for simulation of compressible fluid flow in fractures. Improvements are made to the fluid, contact and coupling components of the existing algorithm to increase its accuracy and stability. The model is successfully benchmarked against the analytical solution for the opening profile of an internally pressurized Griffith fracture, and against the semi-analytical solution for the pressure and opening profile of a bi-wing hydraulic fracture propagating under conditions of no leakoff and no toughness. Additionally, the model is verified through comparison with the results of a hydraulic fracturing experiment that examined propagation of a high-viscosity fracturing fluid in an impermeable medium. Hydraulic fracturing was modeled using the discontinuous deformation analysis.Improvements were made to the existing model׳s fluid, contact and coupling logic.The algorithm was verified against two closed-form solutions and an experiment.